Analyzing the Impact of Legislation on Child Labor in Pakistan - Fasih, Tazeen (World Bank, Washington, DC, 2012)
This paper exploits a natural experiment approach to identify the impact of legislation (Employment of Children Act 1991) in Pakistan on participation of children in the labor markets. The law prohibits employment of children less than 14 years of age in sectors other than agriculture or household enterprises. With micro-data, making use of regression discontinuity data design, the study finds some evidence that the Employment of Children Act 1991 helped in reducing the employment of children immediately after its implementation.